Probenecid inhibits the human bitter taste receptor TAS2R16 and suppresses bitter perception of salicin. - Tiffani A Greene; Suzanne Alarcon; Anu Thomas; Eli Berdougo; Benjamin J Doranz; Paul A S Breslin; Joseph B Rucker (PLoS ONE, 2011)
Bitter taste stimuli are detected by a diverse family of G protein-coupled receptors (GPCRs) expressed in gustatory cells. Each bitter taste receptor (TAS2R) responds to an array of compounds, many of which are toxic and can be found in nature. For example, human TAS2R16 (hTAS2R16) responds to β-glucosides such as salicin, and hTAS2R38 responds to thiourea-containing molecules such as glucosinolates and phenylthiocarbamide (PTC). While many substances are known to activate TAS2Rs, only one inhibitor that specifically blocks bitter receptor activation has been described. Here, we describe a new inhibitor of bitter taste receptors, p-(dipropylsulfamoyl)benzoic acid (probenecid), that acts on a subset of TAS2Rs and inhibits through a novel, allosteric mechanism of action. Probenecid is an FDA-approved inhibitor of the Multidrug Resistance Protein 1 (MRP1) transporter and is clinically used to treat gout in humans. Probenecid is also commonly used to enhance cellular signals in GPCR calcium mobilization assays. We show that probenecid specifically inhibits the cellular response mediated by the bitter taste receptor hTAS2R16 and provide molecular and pharmacological evidence for direct interaction with this GPCR using a non-competitive (allosteric) mechanism. Through a comprehensive analysis of hTAS2R16 point mutants, we define amino acid residues involved in the probenecid interaction that result in decreased sensitivity to probenecid while maintaining normal responses to salicin. Probenecid inhibits hTAS2R16, hTAS2R38, and hTAS2R43, but does not inhibit the bitter receptor hTAS2R31 or non-TAS2R GPCRs. Additionally, structurally unrelated MRP1 inhibitors, such as indomethacin, fail to inhibit hTAS2R16 function. Finally, we demonstrate that the inhibitory activity of probenecid in cellular experiments translates to inhibition of bitter taste perception of salicin in humans. This work identifies probenecid as a pharmacological tool for understanding the cell biology of bitter taste and as a lead for the development of broad specificity bitter blockers to improve nutrition and medical compliance.